2015
DOI: 10.1016/j.vetimm.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

ZAP-70, CTLA-4 and proximal T cell receptor signaling in cows infected with Mycobacterium avium subsp. paratuberculosis

Abstract: Paratuberculosis is a chronic intestinal disease of ruminant animals caused by Mycobacterium avium subsp. paratuberculosis (MAP). A hallmark of paratuberculosis is a transition from a cell-mediated Th1 type response to a humoral Th2 response with the progression of disease from a subclinical to clinical state. The objective of this study was to investigate the expression of two crucial molecules in T cell function, ZAP-70 (zeta-chain-associated protein of 70 kDa) and CTLA-4 (cytotoxic T-lymphocyte antigen-4), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Accordingly, a recent study showed that CD4 ϩ T cells upregulated CTLA-4 in cattle during the subclinical stage of M. avium subsp. paratuberculosis infection (34).…”
Section: Downregulated On Splenic Cd14mentioning
confidence: 99%
“…Accordingly, a recent study showed that CD4 ϩ T cells upregulated CTLA-4 in cattle during the subclinical stage of M. avium subsp. paratuberculosis infection (34).…”
Section: Downregulated On Splenic Cd14mentioning
confidence: 99%
“…The primary aim of this study was to characterize the immune and inflammatory responses of M and P paratuberculosis in sheep, focussing on the nature of the immune dysfunction2128293031 associated with the M disease. TruSeq analysis was used to quantify transcripts expressed in the ICLN of diseased (M and P) and uninfected C animals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the molecular nature of the reduced T cell function in bovine paratuberculosis have identified increased expression of immunoinhibitory molecules in the suppression of anti-MAP T cell responses in vitro 30, and shown a reduction in expression of the T cell receptor second messenger ZAP70 31.…”
mentioning
confidence: 99%
“…The progression of paratuberculosis from subclinical to clinical form is mainly dependent on a gradual shift in immune response from a cell-mediated Th1 type response to a humoral Th2 response [16]. The naive helper T cells mainly differentiate into either Th1 cells or Th2 cells effecter cells after activation.…”
Section: The Role Of Il-10 In Paratuberculosismentioning
confidence: 99%
“…The hallmark of paratuberculosis is shift in immune response from a cell mediated Th1-type response to a humoral T helper2 (Th2) type response with the progression of disease from a subclinical to clinical phase [16]. Similarly, in ovine model of paratuberculosis, it is observed that the cellular immune response attenuates in natural and experimental MAP infected animals in more advanced phase of disease [17].…”
Section: Introductionmentioning
confidence: 99%